Further studies on the hypothesis of PARP-1 inhibition as a strategy for lessening the long-term effects produced by perinatal asphyxia: effects of nicotinamide and theophylline on PARP-1 activity in brain and peripheral tissue : nicotinamide and theophylline on PARP-1 activity - Allende-Castro, Camilo; Gebicke-Härter, Peter J. (Neurotoxicity research, 2012)
Oxygen interruption leads to death when re-oxygenation is not promptly re-established. Re-oxygenation triggers a cascade of biochemical events for restoring function at the cost of improper homeostasis. The effects observed long after perinatal asphyxia (PA) have been explained by over-expression of sentinel proteins, such as poly(ADP-ribose) polymerase-1 (PARP-1), competing for NAD+ during re-oxygenation, leading to the idea that sentinel protein inhibition constitutes a therapeutic strategy. We studied the effects of nicotinamide and theophylline on PARP-1 activity assayed in brain and peripheral (heart) rat tissue 1-24 h after birth, as well as on changes in behaviour and monoamine neurotransmission in adult rats. PA was induced by immersing rat foetuses into a water bath for 0 or 21 min. After resuscitation, the pups were treated with nicotinamide (0.8 mmol/kg, i.p.), theophylline (0.14 mmol/kg, i.p.) or saline (0.9% NaCl) and nurtured by surrogate dams, pending behavioural and microdialysis experiments, or euthanised after birth for assaying PARP-1 activity. To estimate the in vivo distribution of a single dose of nicotinamide or theophylline into brain and peripheral compartment, a series of animals were implanted with microdialysis probes, one into the brain and other subcutaneously, 1 h after birth, assaying the drugs with a HPLC-UV system. Nicotinamide, but not theophylline prevented the long-term effects induced by PA. Only nicotinamide produced a consistent decrease in PARP-1 activity in brain and heart, whether assayed in control or asphyxia-exposed pups. The present results support the idea that the long-term effects induced by PA imply PARP-1 over-activation.